On the report of the Select Committee appointed ?to enquire and report whether any and what steps ought to be taken to simplify the title to land, and to facilitate the transfer thereof, and to prevent frauds on purchasers and mortgagees of land?, and on the first report of Her Majesty's Commissioners appointed ?to enquire into the law relating to the registration of deeds and assurances in Ireland?. - McDonnell, James (Statistical and Social Inquiry Society of Ireland, 1880)
To simplify the title to land and facilitate the transfer thereof must always be a subject of much interest in this country, where so large a proportion of the wealth of the inhabitants consists of land. I will therefore offer no apology for bringing under the notice of the Society this evening the Report (dated 24th June, 1879) of the Select Committee appointed to enquire and report whether any and what steps ought to be taken to simplify the title to land, and to facilitate the transfer thereof, and to prevent frauds on purchasers and mortgagees of land; and also the First Report (dated 12th August, 1879) of Her Majesty's Commissioners appointed to inquire into the law relating to the registration of deeds and assurances in Ireland. The labours of both these bodies extended over the greater part of the years 1878 and 1879, and have produced important proposals for the amendment of the law. The Select Committee treated the question principally as it affected England; the Royal Commission viewed it exclusively in its relation to Ireland.
Read before the Society, 18 November 1879
Keywords: Irish land question; Tenancy laws; Land transfer; Land registration; 314.15